Meningkatkan Hasil Belajar Matematika Dengan Menerapkan Model Pembelajaran Jigsaw - Irwani Hasibuan (JURNAL GLOBAL EDUKASI, 2021)
Abstract: This classroom action research aims to improve the quality of learning for grade VI students at SDN 018443 Chart Asahan in Mathematics for Data Processing through the Jigsaw Learning Model. The research subjects were students of Class VI SDN 018443 Bagan Asahan Kec. Tanjung Balai TP. 2018/2019, totaling 20 students. Based on the discussion, it was concluded that the results of the learning process before the Jigsaw learning model research reached an average value of 66.3. After being motivated, the research was carried out through the first cycle and the second cycle of reflection and the average value recommendation reached 85.4. The results of learning completeness in cycle I reached 80% after cycle I and cycle II, reflection and classical learning completeness recommendations reached 85%. Keywords: data processing; Jigsaw  Abstrak: Penelitian tindakan kelas ini bertujuan untuk meningkatkan kualitas pembelajaran untuk peserta didik kelas VI SDN 018443 Bagan Asahanpada pelajaran Matematika materi Pengolahan Data melalui model Pembelajaran Jigsaw. Subjek penelitian adalah siswa Kelas VI SDN 018443 Bagan Asahan Kec. Tanjung Balai TP. 2018/2019 yang berjumlah 20 orang siswa. Berdasarkan pembahasan pada disimpulkan hasil proses belajar sebelum penelitian model pembelajaran Jigsaw mencapai nilai rata-rata 66,3. setelah termotivasi dilakukan penelitian melalui siklus I dan siklus II refleksi dan rekomendasi nilai rata-rata mencapai 85,4. Hasil ketuntasan belajar pada siklus I mencapai 80% setelah siklus I dan siklus II, refleksi dan rekomendasi ketuntasan belajar klasikal mencapai 85%. Kata Kunci :   Jigsaw; pengolahan data